2019
DOI: 10.21276/aan.2019.4.2.33
|View full text |Cite
|
Sign up to set email alerts
|

A Randomised Control Study Comparing Hemodynamic Response to Laryngoscopy & Endotracheal Intubation with Macintosh Direct Laryngoscope & C-Mac Video Laryngoscope In Adult Patients

Abstract: Background: Aim: The aim of the present study is to assess and compare the efficacy of Macintosh laryngoscope with C-MAC video laryngoscope in attenuating the hemodynamic stress responses to laryngoscopy and endotracheal intubation. Subjects and Methods: A total of 60 patients of ASA grade I or II who were admitted in the hospital for general anaesthesia were included in the study. The total number of patients was randomly divided into two groups containing 30 patients each. In one of the group the endotrachea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 26 publications
3
2
0
Order By: Relevance
“…In our study, the mean diastolic blood pressure was found to be statistically significant in Group M as compared to Group V at ETI1 and ETI3. This is in accordance with the findings of Kumar et al [11] and Archana et al [17]. On the contrary, Rajan et al [10] observed that there was no statistically significant difference in the diastolic blood pressure in traditional Macintosh laryngoscope group and VL group.…”
Section: Singh Et Alsupporting
confidence: 90%
See 4 more Smart Citations
“…In our study, the mean diastolic blood pressure was found to be statistically significant in Group M as compared to Group V at ETI1 and ETI3. This is in accordance with the findings of Kumar et al [11] and Archana et al [17]. On the contrary, Rajan et al [10] observed that there was no statistically significant difference in the diastolic blood pressure in traditional Macintosh laryngoscope group and VL group.…”
Section: Singh Et Alsupporting
confidence: 90%
“…In our study, the difference in mean SPO 2 and mean ETCO 2 between the two groups was found to be non-significant at any time interval. Similar results in terms of SPO 2 were also obtained in study by Kumar et al [11].…”
Section: Singh Et Alsupporting
confidence: 90%
See 3 more Smart Citations